The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/jacs.2c04080
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Oxazinomycin Biosynthetic Pathway Revealing the Key Role of a Nonheme Iron-Dependent Mono-oxygenase

Abstract: Oxazinomycin is a C-nucleoside natural product with antibacterial and antitumor activities. In addition to the characteristic C-glycosidic linkage shared with other C-nucleosides, oxazinomycin also features a structurally unusual 1,3-oxazine moiety, the biosynthesis of which had previously been unknown. Herein, complete in vitro reconstitution of the oxazinomycin biosynthetic pathway is described. Construction of the C-glycosidic bond between ribose 5-phosphate and an oxygen-labile pyridine heterocycle is cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 53 publications
0
32
0
Order By: Relevance
“…194,195 The reaction of OzmD produces cyanide as a byproduct in addition to 163, as confirmed by a chemical derivatization method. 195 The released cyanide molecule originates from C3− NH 2 of 162, as verified by in vitro assays with 13 C-or 15 N-labeled substrates, which is in good agreement with an early feeding experiment with [2-14 C]-L-Glu. Furthermore, a series of 18 O labeling experiments indicated that the two carbonyl oxygens in 163 are retained during the OzmD-catalyzed reaction, while the alkoxy oxygen of 163 is derived from O 2 .…”
Section: C−c Bond Cleavage Reactionsmentioning
confidence: 77%
See 4 more Smart Citations
“…194,195 The reaction of OzmD produces cyanide as a byproduct in addition to 163, as confirmed by a chemical derivatization method. 195 The released cyanide molecule originates from C3− NH 2 of 162, as verified by in vitro assays with 13 C-or 15 N-labeled substrates, which is in good agreement with an early feeding experiment with [2-14 C]-L-Glu. Furthermore, a series of 18 O labeling experiments indicated that the two carbonyl oxygens in 163 are retained during the OzmD-catalyzed reaction, while the alkoxy oxygen of 163 is derived from O 2 .…”
Section: C−c Bond Cleavage Reactionsmentioning
confidence: 77%
“…The unique pyridine base is derived from l -glutamine via the sugar-linked aminopyridine 162 as the intermediate. In vitro assays demonstrated that the unusual rearrangement reaction of 162 to 163 is catalyzed by OzmD. , …”
Section: Mononuclear Nonheme Iron Enzymesmentioning
confidence: 99%
See 3 more Smart Citations